Hubungan Antara Pengetahuan Dan Sikap Ibu Rumah Tangga Dengan Kondisi Sanitasi Rumah Di Kelurahan Semanggi Kota Surakarta Tahun 2016 - NUGRAHANINGSIH, DYKA (2016)
House sanitary strived to maintain the health of house occupants and the environment around the house. People who are most instrumental in maintaining cleanliness and sanitation within the house is a housewife. The purpose of this study was to know the relation between knowledge and attitude of housewife with house sanitary conditions in Semanggi village Surakarta city in 2016. The method was used in observational with cross sectional approach. The study population as many as 4,682 homes, and 98 samples were taken with Systematic Random Sampling. Statistical test using Chi-Square with the help of computer program applications, with a significance level of 0.05. The results showed that 51.2% housewifes have good knowledge, 54.08% have good attitude, and 78.57% of the houses have an unhygienic condition. The conclusion was that there is no correlation between knowledge (p = 0.106) and attitude (p = 0.751) of housewife with house sanitary conditions in Semanggi village Surakarta city in 2016.